Remote controlled lawn mower using SK40C with PIC16F877A microcontroller: article / Mohd. Ameerul Asyraf Abdul Rahim - Abdul Rahim, Mohd. Ameerul Asyraf (2013)
A remote controlled lawnmower robot that uses a PIC16F877A microcontroller was presented in this project. The remote controlled lawnmower robot is designed to be able to follow the command given via a PlayStation 2 (PS2) controller joystick whether to move forward, backward, turn right and left to mow grass. The Remote Controlled Lawnmower's system principle is to remotely control a lawnmower by using a PS2 controller joystick. The microcontroller that will be used for this project is PIC16F877A. The remote controlled lawn mower can be separated into three main parts which is the input, the controller and the output. The input is the movement control by human via a remote control. User will control the lawnmower by using a remote control to which part of lawn to be mowed. The controller which is the brain of the system, will received the information signal that are send by the input to be processed and then send an output signal to the output part so that the output can perform its task. The output for this project is lawnmower's movement wheels that use two RC servo motor and the DC motor for cutting.